Pengaruh Produksi dan Harga Gambir terhadap Perekonomian Masyarakat Nagari Rawang Lampanjang Kecamatan Sutera Kabupaten Pesisir Selatan - Harahap, Romi Rianto; Anrizal, Sri Yulia; Rahman, Lisa Fitriani; Anjasmara, Wing (Jurnal Profiet, 2024)
This study discusses the influence of gambir production and price on the economy of the people of Nagari Rawang Lampanjang. The results of the study indicate that gambir production has a significant influence on the economy, as evidenced by the t-count value which is greater than the t-table and a low significance value. In addition, the price of gambir also has a significant influence on the economy, as indicated by the t-count value which is greater than the t-table and a low significance value. Simultaneously, gambir production and price have a significant influence on the economy, as indicated by the results of the f-test. Therefore, increasing production and stabilizing the price of gambir can have a positive impact on the economy of the people of Nagari Rawang Lampanjang. Keywords: Price, Production, Economy